Efficient cycling utilization of solar-thermal energy for thermochromic displays with controllable heat output. Issue 1 (28th September 2018) - Yang, Weixiang; Feng, Yiyu; Si, Qianyu; Yan, Qinghai; Long, Peng; Dong, Liqi; Fu, Linxia; Feng, Wei
Abstract : Photo-thermal energy cycles for thermochromic displays with control of heat output. Abstract : Use of solar energy as a source of heat is an important method of storing and providing clean energy for thermal management. However, the difficulties associated with combining the high-energy storage and high-rate heat release of solar thermal storage (STS) lower their ability to output heat controllably, and thus, prevent their application in temperature-sensitive or temperature-responsive systems. Herein, we report for the first time the closed-cycle utilization of photo-thermal energy for thermochromic displays by optimizing the solid-state high-rate heat output of STS films. By controlling the molecular interaction, a tri-azobenzene (Azo)-based templated assembly can be made to combine a maximum energy density of 150.3 W h kg −1, a long half-life (1250 h), and a high power density of 3036.9 W kg −1 . The STS film can induce a reversible color change in a complicated thermochromic-patterned display by releasing heat to increase the temperature by 6–7 °C. We also realize variable heat release by controlling the heating rate and temperature to utilize photo-thermal energy efficiently. Efficient cycling utilization of photo-thermal energy using a tri-Azo assembly could be used to harness photo-thermal power for thermal management.